Assessing the Moderating Role of Organizational Culture on the Effect of Knowledge Networks on Firm Innovation in Visegrad Countries: The Perspective of Knowledge Production Function - Arthur, Emmanuel Ebo; Stejskal, Jan (Academic Conferences and Publishing International Limited, 2024)
Our study is based on open innovation theory and the KPF. Adopting the 2018 cross-sectional CIS data from the Eurostat database for the four Visegrad countries (Czech Republic, Poland, Hungary, and Slovakia), the OLS regression and Average Marginal Effects models were used for the analysis. We confirmed that when firms co-operate on R&D, there is a positive and significant effect on radical innovation but negative significant effect on incremental innovation. Firm co-operation on innovation activities excluding R&D has positive and significant effect on both radical and incremental innovations. Other business co-operations had positive and significant effect on incremental innovation but not on radical innovation. We further confirmed a positive significant moderating role on the effect of R&D co-operation on radical innovation. We proposed theoretical and practical implications of our study to firm managers, government, and policy formulators.
Odhalení moderační role vlivu organizační kultury na znalostní sítě a firemní inovace v zemích Visegrádu
Keywords: R&D co-operation; Training and Development; Radical and Incremental Innovations; OLS; Visegrad